Vinyl chloride resin composition, vinyl chloride resin molded article, and laminate
Patent Information
- Application Number
- JP2025059871
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0022】 本発明によれば、ティアラインを設けることなく、高温環境下および低温環境下でもエアバックを適切に展開可能な塩化ビニル樹脂成形体を形成可能な塩化ビニル樹脂組成物を提供することができる。 また、本発明によれば、上記塩化ビニル樹脂組成物から形成された塩化ビニル樹脂成形体、および、該塩化ビニル樹脂成形体を有する積層体を提供することができる。
Smart Images

Figure 2026166726000001 
Figure 2026166726000002
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a vinyl chloride resin composition, a vinyl chloride resin molded article, and a laminate.
BACKGROUND ART
[0002] Vinyl chloride resins are generally excellent in properties such as cold resistance, heat resistance, and oil resistance, and are thus used in a variety of applications. Specifically, for example, for forming automotive interior parts such as automotive instrument panels and door trims, automotive interior materials such as skins made of vinyl chloride resin molded articles and laminates formed by lining a skin made of a vinyl chloride resin molded article with a foam such as polyurethane foam are used.
[0003] The vinyl chloride resin molded article used as the skin is produced, for example, by molding a vinyl chloride resin composition containing a vinyl chloride resin and a plasticizer using a known molding method such as powder slush molding.
[0004] Here, in automotive instrument panels and the like, a technique is known in which shallow cuts (tear lines) are formed on the back surface of the skin (the surface lined with a foam such as polyurethane foam; the same applies hereinafter) to facilitate deployment of the airbag during operation of the airbag and prevent scattering of the skin (see, for example, Patent Document 1).
[0005] Specifically, Patent Document 1 discloses an airbag door for an automobile in which an airbag door is integrally formed on an instrument panel laminated by bonding a surface material having a foam layer adhered to the surface to a base material, and a tear line is formed on the door base material portion of the base material for rupturing and deploying when the airbag is activated, wherein the adhesive force of the foam layer to the door base material portion is set to a peel strength of at least 10 N / 25 mm width, and the surface material has a surface-only breaking strength of 1.4 to 12.0 MPa, a surface-only breaking elongation of 200 to 600%, and a peel strength between the surface and the foam layer is set in the range of 10 to 50 N / 25 mm width. [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] International Publication No. 2009 / 141863 [Overview of the Initiative] [Problems that the invention aims to solve]
[0007] However, while the presence of tear lines allows for proper airbag deployment in high-temperature environments, in low-temperature environments, changes in the physical properties of the skin may prevent the airbag from deploying properly even with tear lines, resulting in insufficient airbag deployment capability. Furthermore, forming tear lines on the back surface of the skin requires a separate tear line formation process, which reduces the manufacturing efficiency of the skin. Moreover, forming tear lines on the back surface of the skin can cause the tear lines to become visible on the surface of the skin (the side opposite to the back surface) when the skin shrinks due to heat, resulting in a deterioration of the skin's appearance.
[0008] Therefore, there was a need to develop a new skin technology that would provide excellent airbag deployment performance not only in high-temperature environments but also in low-temperature environments, and that would eliminate the need for tear lines.
[0009] Therefore, the present invention aims to provide a vinyl chloride resin composition that can form a vinyl chloride resin molded article capable of properly deploying an airbag even in high-temperature and low-temperature environments without providing a tear line. Furthermore, the present invention aims to provide a vinyl chloride resin molded article formed from the above-mentioned vinyl chloride resin composition, and a laminate having the vinyl chloride resin molded article. [Means for solving the problem]
[0010] The inventors diligently conducted research with the aim of solving the above problems. As a result, the inventors have newly discovered that by using a vinyl chloride resin composition (d) comprising (a) a matrix vinyl chloride resin, (b) a plasticizer, and (c) an inorganic substance having a predetermined melting point, wherein the ratio of tensile elongations measured under different predetermined temperature conditions when molded into a sheet is less than or equal to a predetermined value, it is possible to obtain a vinyl chloride resin molded article that can appropriately deploy airbags even in high-temperature and low-temperature environments without providing a tear line, and thus completed the present invention.
[0011] In other words, the present invention aims to advantageously solve the above problems, and the present invention is a vinyl chloride resin composition comprising [1](a) a matrix vinyl chloride resin, (b) a plasticizer, and (c) an inorganic substance, wherein when formed into a sheet, the ratio of the tensile elongation [ε1] measured at 85°C to the tensile elongation [ε2] measured at -35°C ([ε1] / "ε2") is 15 or less, and the (c) inorganic substance has a higher melting point than the vinyl chloride resin composition. Thus, by using a polyvinyl chloride resin composition in which the ratio of tensile elongation measured under different predetermined temperature conditions when molded into a sheet is below a predetermined value, it is possible to obtain a polyvinyl chloride resin molded article that can properly deploy airbags even in high-temperature and low-temperature environments without the need for tear lines. In this invention, the tensile elongations [ε1] and [ε2] of the sheet can be measured in accordance with ISO 527-2 by the method described in the examples. In this invention, the melting point of the vinyl chloride resin composition refers to a temperature range of 180°C to 280°C, which is the temperature range in which the maximum endothermic peak is observed in the TG-DTA curve in the range of 40°C to 300°C, obtained by measuring the melting point of the vinyl chloride resin composition in air under conditions where the sample is heated from approximately 40°C to approximately 300°C at a heating rate of 10°C / min using differential thermal-thermogravimetric analysis (TG-DTA).
[0012] [2] In the vinyl chloride resin composition described in [1] above, the content of the plasticizer (b) is preferably 90 parts by mass or more per 100 parts by mass of the matrix vinyl chloride resin (a). In this way, if the content of the plasticizer is above the lower limit, a vinyl chloride resin molded article can be obtained in which the airbag can be deployed more appropriately even in high-temperature and low-temperature environments without the need for a tear line.
[0013] [3] In the vinyl chloride resin composition of [1] or [2] above, the content of the inorganic substance (c) is preferably 35 parts by mass or less per 100 parts by mass of the matrix vinyl chloride resin (a). In this way, if the content of the inorganic substance is below the above upper limit, a vinyl chloride resin molded article can be obtained in which the airbag can be deployed more appropriately even in high-temperature and low-temperature environments without providing a tear line.
[0014] [4] The vinyl chloride resin compositions described in [1] to [3] above preferably further contain vinyl chloride resin fine particles. By further including vinyl chloride resin fine particles in this way, the fluidity of the vinyl chloride resin composition can be increased.
[0015] [5] In any of the vinyl chloride resin compositions described in [1] to [4] above, it is preferable that the plasticizer (b) contains at least one of trimellitic acid ester and sebatic acid ester. By including at least one of trimellitic acid ester and sebatic acid ester as the plasticizer, a vinyl chloride resin molded article can be obtained in which the airbag can be deployed more appropriately even in high-temperature and low-temperature environments without the need for a tear line.
[0016] [6] Any of the vinyl chloride resin compositions described in [1] to [5] above is preferably used for powder molding. When a vinyl chloride resin composition is used for powder molding, a vinyl chloride resin molded article that can be used well as an automotive interior material, such as the surface of an automotive instrument panel, can be easily obtained.
[0017] [7] Any of the vinyl chloride resin compositions described in [1] to [6] above is preferably used in powder slush molding. Using a vinyl chloride resin composition in powder slush molding makes it easier to obtain a vinyl chloride resin molded article that can be used well as an automotive interior material, such as the surface of an automotive instrument panel.
[0018] Furthermore, this invention aims to advantageously solve the above problems, and the present invention is a vinyl chloride resin molded article obtained by molding any of the vinyl chloride resin compositions described in [1] to [7] above. Thus, a vinyl chloride resin molded article obtained by molding the above-described vinyl chloride resin composition can be used as an automotive interior material because it can properly deploy airbags even in high-temperature and low-temperature environments without the need for tear lines.
[0019] [9] The vinyl chloride resin molded article described in [8] above is preferably for use as the surface of an automotive instrument panel. If the vinyl chloride resin molded article of the present invention is used as the surface of an automotive instrument panel, it is possible to manufacture an automotive instrument panel having a surface that allows the airbag to be properly deployed even in high-temperature and low-temperature environments without the need for tear lines.
[0020] Further, the present invention aims to advantageously solve the above problems, and the present invention is a laminate comprising the polyurethane foam molded article of
[10] and the vinyl chloride resin molded article according to the above [8] or [9]. As described above, the laminate having the polyurethane foam molded article and any one of the vinyl chloride resin molded articles described above is provided with a vinyl chloride resin molded article portion that allows an airbag to be properly deployed even in a high-temperature environment and a low-temperature environment without providing a tear line.
[0021]
[11] The laminate of the above
[10] is preferably for automotive instrument panels. When the above laminate is used for an automotive instrument panel, it is possible to produce an automotive instrument panel having a skin that allows an airbag to be properly deployed even in a high-temperature environment and a low-temperature environment without providing a tear line. Effects of the Invention
[0022] According to the present invention, it is possible to provide a vinyl chloride resin composition capable of forming a vinyl chloride resin molded article that allows an airbag to be properly deployed even in a high-temperature environment and a low-temperature environment without providing a tear line. Further, according to the present invention, it is possible to provide a vinyl chloride resin molded article formed from the above vinyl chloride resin composition, and a laminate having the vinyl chloride resin molded article. Modes for Carrying Out the Invention
[0023] Hereinafter, embodiments of the present invention will be described in detail. Here, the vinyl chloride resin composition of the present invention can be used, for example, when forming the vinyl chloride resin molded article of the present invention. The vinyl chloride resin molded article formed using the vinyl chloride resin composition of the present invention can be suitably used as an automotive interior material, such as a skin included in automotive interior parts such as automotive instrument panels and door trims. Furthermore, the vinyl chloride resin molded article of the present invention can be used, for example, when forming the laminate of the present invention. The laminate formed using the vinyl chloride resin molded article of the present invention can be suitably used as an automotive interior material when manufacturing automotive interior parts such as automotive instrument panels and door trims.
[0024] (Vinyl chloride resin composition) The vinyl chloride resin composition of the present invention comprises (a) a matrix vinyl chloride resin, (b) a plasticizer, and (c) an inorganic substance having a higher melting point than the vinyl chloride resin composition, and optionally further comprises or omits other components other than the above-mentioned (a) matrix vinyl chloride resin, (b) plasticizer, and (c) inorganic substance. Furthermore, the vinyl chloride resin composition of the present invention is characterized in that, when molded into a sheet, the ratio of the tensile elongation [ε1] measured at 85°C to the tensile elongation [ε2] measured at -35°C ([ε1] / "ε2") is 15 or less.
[0025] Furthermore, according to the vinyl chloride resin composition of the present invention, it is possible to form a vinyl chloride resin molded article that can properly deploy airbags even in high-temperature and low-temperature environments without providing tear lines (hereinafter also simply referred to as "excellent airbag deployment performance in high-temperature and low-temperature environments").Therefore, by using the vinyl chloride resin composition of the present invention, it is possible to obtain a vinyl chloride resin molded article suitable as an automotive interior material, such as an instrument panel cover and a door trim cover, that can properly deploy airbags even in high-temperature and low-temperature environments without providing tear lines.Here, for example, from the viewpoint of easily obtaining a vinyl chloride resin molded article that can be used well as an automotive interior material using the vinyl chloride resin composition of the present invention, it is preferable that the vinyl chloride resin composition of the present invention be used in powder molding, and more preferably in powder slush molding.
[0026] <[ε1] / 「ε2」> As described above, the vinyl chloride resin composition of the present invention requires that, when molded into a sheet, the ratio of the tensile elongation [ε1] measured at 85°C to the tensile elongation [ε2] measured at -35°C ([ε1] / "ε2") is 15 or less. If the value of [ε1] / "ε2" exceeds 15, airbag deployment in high-temperature and low-temperature environments cannot be ensured. From the viewpoint of further improving airbag deployment in high-temperature and low-temperature environments, the value of [ε1] / "ε2" is preferably 12 or less, more preferably 10 or less, and even more preferably 8 or less. The lower limit of [ε1] / "ε2" is not particularly limited, but is usually 2 or more. Here, [ε1] / "ε2" represents the temperature dependence of the tensile elongation of a molded article (sheet) of the polyvinyl chloride resin composition. A lower value of [ε1] / "ε2" indicates that the sheet stretches more easily at low temperatures and does not stretch excessively at high temperatures (i.e., the temperature dependence of the tensile elongation is smaller).
[0027] <[ε1]> The tensile elongation [ε1] at 85°C is not particularly limited, but is preferably 250% or more, preferably 300% or more, preferably 500% or less, and more preferably 450% or less. The value of [ε1] can be adjusted as appropriate, for example, by adjusting the amount of (b) plasticizer and / or (c) inorganic substances contained in the vinyl chloride resin composition.
[0028] <[ε2]> The tensile elongation [ε2] at -35℃ is not particularly limited, but is preferably 30% or more, and preferably 40% or more. The value of [ε2] can be adjusted as appropriate, for example, by adjusting the amount of (b) plasticizer and / or (c) inorganic substances contained in the vinyl chloride resin composition.
[0029] The melting point of the vinyl chloride resin composition is not particularly limited as long as it is lower than the melting point of the inorganic substance, but for example it may be between 180°C and 280°C.
[0030] (a) Matrix polyvinyl chloride resin (a) The matrix vinyl chloride resin is resin particles made of vinyl chloride resin. (a) The matrix vinyl chloride resin typically functions as the matrix resin in a vinyl chloride resin composition. Furthermore, (a) as the vinyl chloride resin constituting the matrix vinyl chloride resin, in addition to a homopolymer of vinyl chloride, copolymers (vinyl chloride copolymers) containing preferably 50% by mass or more, more preferably 70% by mass or more, of vinyl chloride units are included. In this invention, "resin particles" refers to particles with a particle diameter of 30 μm or more. Specific examples of monomers (comonomers) copolymerizable with vinyl chloride in vinyl chloride copolymers include: olefins such as ethylene and propylene; halogenated olefins such as allyl chloride, vinylidene chloride, vinyl fluoride, and trifluoroethylene chloride; vinyl carboxylate esters such as vinyl acetate and vinyl propionate; vinyl ethers such as isobutyl vinyl ether and cetyl vinyl ether; allyl ethers such as allyl-3-chloro-2-oxypropyl ether and allyl glycidyl ether; acrylic acid, maleic acid, itaconic acid, and acrylic acid-2-hydroxypropyl acrylate. Examples include unsaturated carboxylic acids such as droxyethyl methyl methacrylate, monomethyl maleate, diethyl maleate, and maleic anhydride, their esters, or acid anhydrides; unsaturated nitriles such as acrylonitrile and methacrylonitrile; acrylamides such as acrylamide, N-methylolacrylamide, acrylamide-2-methylpropanesulfonic acid, and (meth)acrylamidopropyltrimethylammonium chloride; allylamines such as allylamine benzoate and diallyldimethylammonium chloride, and their derivatives; and so on. The monomers exemplified above are only a part of the comonomers, and various monomers exemplified in "Polyvinyl Chloride" edited by the Vinyl Division of the Kinki Chemical Association, Nikkan Kogyo Shimbun (1988), pp. 75-104, can be used as comonomers. One or more of these monomers can be used. The vinyl chloride resin constituting the above (a) matrix vinyl chloride resin also includes resins in which (1) vinyl chloride or (2) vinyl chloride and the copolymer are graft polymerized on resins such as ethylene-vinyl acetate copolymer, ethylene-methyl methacrylate copolymer, ethylene-ethyl acrylate copolymer, and chlorinated polyethylene. In this specification, "(meth)acrylic" means acrylic and / or methacrylic.
[0031] Here, the vinyl chloride resin constituting the matrix vinyl chloride resin described above (a) can be produced by any of the conventionally known production methods, such as suspension polymerization, emulsion polymerization, solution polymerization, or bulk polymerization. In particular, vinyl chloride resin produced by suspension polymerization is preferred as the vinyl chloride resin constituting the matrix vinyl chloride resin (a).
[0032] Furthermore, the average particle size of the matrix vinyl chloride resin (a) is preferably 50 μm or more, more preferably 100 μm or more, more preferably 500 μm or less, more preferably 250 μm or less, and even more preferably 200 μm or less. When the average particle size of the matrix vinyl chloride resin (a) is within the above range, the powder flowability of the vinyl chloride resin composition is good, and the smoothness of the vinyl chloride resin molded article formed by molding the vinyl chloride resin composition is improved. In this invention, (a) the average particle size of the matrix vinyl chloride resin can be measured as a volume-average particle diameter by laser diffraction in accordance with JIS Z8825.
[0033] The average degree of polymerization of the vinyl chloride resin constituting the matrix vinyl chloride resin described above (a) is preferably 800 or higher, preferably 5000 or lower, more preferably 3000 or lower, even more preferably 2200 or lower, and particularly preferably 2000 or lower. When the average degree of polymerization of the matrix vinyl chloride resin described above (a) is within the above range, good heat resistance can be imparted to the vinyl chloride resin molded article obtained by molding the vinyl chloride resin composition. The "average degree of polymerization" is measured in accordance with JIS K 6720-2.
[0034] The glass transition temperature of the vinyl chloride resin constituting the matrix vinyl chloride resin described above (a) is not particularly limited as long as it is lower than the melting point of the inorganic material (c), but for example it may be between 70°C and 90°C. The glass transition temperature of polyvinyl chloride resin can be measured using a differential scanning calorimeter (DSC). Specifically, a sample of polyvinyl chloride resin is heated from -10°C to 200°C at a rate of 20°C / min, held at 200°C for 3 minutes, rapidly cooled at a rate of 20°C / min, and then heated again from -10°C to 200°C at a rate of 20°C / min. The temperature at the inflection point of the graph plotting the amount of heat generated against temperature can then be determined as the glass transition temperature.
[0035] <(b) Plasticizers> (b) Examples of plasticizers that can be used include the following primary and secondary plasticizers.
[0036] As for so-called primary plasticizers, Trimellit acid esters such as tri-n-hexyl trimellitate, tri-n-heptyl trimellitate, tri-n-octyl trimellitate, tri-(2-ethylhexyl) trimellitate, tri-n-nonyl trimellitate, tri-n-decyl trimellitate, triisodecyl trimellitate, tri-n-undecyl trimellitate, tri-n-dodecyl trimellitate, tri-n-alkyl trimellitate (esters having two or more alkyl groups with different carbon numbers [however, the number of carbon atoms is between 6 and 12] in the molecule), and trialkyl trimellitate (esters having two or more alkyl groups with different carbon numbers [however, the number of carbon atoms is between 8 and 10] in the molecule); Pyromellitic esters such as tetra-n-hexyl pyromellitic acid, tetra-n-heptyl pyromellitic acid, tetra-n-octyl pyromellitic acid, tetra-(2-ethylhexyl) pyromellitic acid, tetra-n-nonyl pyromellitic acid, tetra-n-decyl pyromellitic acid, tetraisodecyl pyromellitic acid, tetra-n-undecyl pyromellitic acid, tetra-n-dodecyl pyromellitic acid, and tetra-n-alkyl pyromellitic acid esters (esters having two or more alkyl groups with different numbers of carbon atoms [however, the number of carbon atoms is between 6 and 12] in the molecule); Phthalic acid derivatives such as dimethyl phthalate, diethyl phthalate, dibutyl phthalate, di-(2-ethylhexyl) phthalate, di-n-octyl phthalate, diisobutyl phthalate, diheptyl phthalate, diphenyl phthalate, diisodecyl phthalate, ditridecyl phthalate, diundecyl phthalate, dibenzyl phthalate, butylbenzyl phthalate, dinonyl phthalate, and dicyclohexyl phthalate; Isophthalic acid derivatives such as dimethyl isophthalate, di-(2-ethylhexyl) isophthalate, and diisooctyl isophthalate; Tetrahydrophthalic acid derivatives such as di-(2-ethylhexyl)tetrahydrophthalate, di-n-octyltetrahydrophthalate, and diisodecyltetrahydrophthalate; Adipic acid derivatives such as di-n-butyl adipate, di(2-ethylhexyl) adipate, diisodecyl adipate, and diisononyl adipate; Azelaic acid derivatives such as di-(2-ethylhexyl)azelate, diisooctylazelate, and di-n-hexylazelate; Sebacate derivatives (sebacate esters) such as di-n-butyl sebacate, di-(2-ethylhexyl) sebacate, diisodecyl sebacate, and di-(2-butyloctyl) sebacate; Maleic acid derivatives such as di-n-butyl maleate, dimethyl maleate, diethyl maleate, and di-(2-ethylhexyl) maleate; Fumaric acid derivatives such as di-n-butyl fumarate and di-(2-ethylhexyl) fumarate; Citric acid derivatives such as triethyl citrate, tri-n-butyl citrate, acetyl triethyl citrate, and acetyl tri-(2-ethylhexyl) citrate; Itaconic acid derivatives such as monomethyl itaconate, monobutyl itaconate, dimethyl itaconate, diethyl itaconate, dibutyl itaconate, and di-(2-ethylhexyl) itaconate; Oleic acid derivatives such as butyloleate, glyceryl monooleate, and diethylene glycol monooleate; Ricinoleic acid derivatives such as methylacetyl ricinolate, butylacetyl ricinolate, glyceryl monoricinolate, and diethylene glycol monoricinolate; Stearic acid derivatives such as n-butyl stearate and diethylene glycol distearate; Diethylene glycol monolaurate, diethylene glycol diperargonate, pentaerythritol fatty acid esters, and other fatty acid derivatives; Phosphate derivatives such as triethyl phosphate, tributyl phosphate, tri-(2-ethylhexyl) phosphate, tributoxyethyl phosphate, triphenyl phosphate, cresyldiphenyl phosphate, tricresyl phosphate, trixylenyl phosphate, and tris(chloroethyl) phosphate; Glycol derivatives such as diethylene glycol dibenzoate, dipropylene glycol dibenzoate, triethylene glycol dibenzoate, triethylene glycol di-(2-ethyl butyrate), triethylene glycol di-(2-ethylhexoate), and dibutylmethylene bisthioglycolate; Glycerol derivatives such as glycerol monoacetate, glycerol triacetate, and glycerol triptylate; Epoxy derivatives such as diisodecyl epoxyhexahydrophthalate, epoxy triglycerides, octyl epoxidized oleate, and decyl epoxidized oleate; Examples of polyester plasticizers include polyesters containing structural units derived from adipic acid (adipic acid-based polyesters), polyesters containing structural units derived from sebaciic acid (sebacic acid-based polyesters), and polyesters containing structural units derived from phthalic acid (phthalic acid-based polyesters).
[0037] Furthermore, examples of so-called secondary plasticizers include epoxidized vegetable oils such as epoxidized soybean oil and epoxidized linseed oil; chlorinated paraffin; glycol fatty acid esters such as triethylene glycol dicaprylate; butyl epoxy stearate; phenyloleate; and methyl dihydroabiethinate.
[0038] Furthermore, these plasticizers may be used individually, or two or more may be used in combination, for example, a primary plasticizer and a secondary plasticizer. In addition, when a secondary plasticizer is used, it is preferable to use it in combination with a primary plasticizer of equal or greater mass than the secondary plasticizer.
[0039] Furthermore, among the plasticizers mentioned above, from the viewpoint of further improving airbag deployment in high-temperature and low-temperature environments, it is preferable to use at least one of trimellitic acid esters and sebacilic acid derivatives, more preferably trimellitic acid esters and sebacilic acid derivatives (esters), even more preferably branched trimellitic acid esters and sebacilic acid derivatives, and even more preferably trimellitic acid tri-(2-ethylhexyl) and diisodecyl sebacate.
[0040] [Content percentage] (b) The content ratio of plasticizers (total content ratio if two or more types of plasticizers are used) is preferably 80 parts by mass or more, more preferably 90 parts by mass or more, preferably 200 parts by mass or less, and more preferably 180 parts by mass or less per 100 parts by mass of matrix vinyl chloride resin. (b) If the content ratio of plasticizers is above the lower limit above, the tensile elongation of the vinyl chloride resin molded article formed using the vinyl chloride resin composition can be maintained well at low temperatures. Also, (b) if the content ratio of plasticizers is below the upper limit above, stickiness due to plasticizers in the vinyl chloride resin composition and the vinyl chloride resin molded article can be suppressed.
[0041] Furthermore, (b) when the plasticizer contains trimellitic acid ester, the trimellitic acid ester content is preferably 40 parts by mass or more, more preferably 45 parts by mass or more, preferably 200 parts by mass or less, and more preferably 180 parts by mass or less, per 100 parts by mass of the matrix vinyl chloride resin. If the trimellitic acid ester content is above the lower limit, the tensile elongation at low temperatures of the vinyl chloride resin molded article formed using the vinyl chloride resin composition can be maintained well. Also, if the trimellitic acid ester content is below the upper limit, stickiness due to the plasticizer in the vinyl chloride resin composition and the vinyl chloride resin molded article can be suppressed.
[0042] Furthermore, the trimellitic acid ester content is preferably 40% by mass or more, more preferably 60% by mass or more, preferably 100% by mass or less, and more preferably 98% by mass or less, based on (b) the total content of plasticizers (100% by mass). If the trimellitic acid ester content is above the lower limit above, the tensile elongation of the vinyl chloride resin molded article formed using the vinyl chloride resin composition can be maintained well at low temperatures. Also, if the trimellitic acid ester content is below the upper limit above, stickiness due to plasticizers in the vinyl chloride resin composition and the vinyl chloride resin molded article can be suppressed.
[0043] Furthermore, (b) when the plasticizer contains a sebaciate derivative, the content of the sebaciate derivative is preferably 5 parts by mass or more, preferably 15 parts by mass or more, preferably 50 parts by mass or less, and more preferably 40 parts by mass or less, per 100 parts by mass of the matrix vinyl chloride resin. If the content of the sebaciate derivative is above the lower limit, the tensile elongation at low temperatures of the vinyl chloride resin molded article formed using the vinyl chloride resin composition can be maintained well. Also, if the content of the sebaciate derivative is below the upper limit, stickiness due to the plasticizer in the vinyl chloride resin composition and the vinyl chloride resin molded article can be suppressed.
[0044] Furthermore, the content of the sebaci acid derivative is preferably 5% by mass or more, more preferably 10% by mass or more, usually less than 100% by mass, preferably 55% by mass or less, and more preferably 35% by mass or less, based on (b) the total content of plasticizers (100% by mass). If the content of the sebaci acid derivative is above the lower limit, the tensile elongation of the vinyl chloride resin molded article formed using the vinyl chloride resin composition can be maintained well at low temperatures. Also, if the content of the sebaci acid derivative is below the upper limit, stickiness due to plasticizers in the vinyl chloride resin composition and the vinyl chloride resin molded article can be suppressed.
[0045] Furthermore, (b) when both trimellitic acid ester and sebacic acid derivative are included as plasticizers, the total content of trimellitic acid ester and sebacic acid derivative is preferably 90 parts by mass or more, more preferably 95 parts by mass or more, preferably 170 parts by mass or less, and preferably 160 parts by mass or less, per 100 parts by mass of the matrix vinyl chloride resin. If the content of trimellitic acid ester and sebacic acid derivative is above the lower limit above, the tensile elongation at low temperatures of the vinyl chloride resin molded article formed using the vinyl chloride resin composition can be maintained well. Furthermore, if the content of trimellitic acid ester and sebacic acid derivative is below the upper limit above, stickiness due to the plasticizer in the vinyl chloride resin composition and the vinyl chloride resin molded article can be suppressed. (b) When both trimellitic acid ester and sebacic acid derivative are included as plasticizers, the preferred content ratios of trimellitic acid ester and sebacic acid derivative are the same as the preferred content ratios of trimellitic acid ester and sebacic acid derivative described above.
[0046] Furthermore, if other plasticizers other than trimellitic acid esters and sebacic acid derivatives are included, their content is preferably 0.1 parts by mass or more, more preferably 1 part by mass or more, even more preferably 2 parts by mass or more, preferably 30 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, per 100 parts by mass of the matrix vinyl chloride resin. If the content of other plasticizers other than trimellitic acid esters and sebacic acid derivatives is within the above range, a vinyl chloride resin molded article with better tensile elongation at low temperatures can be produced more easily.
[0047] <(c) Inorganic substances> The (c) inorganic substance included in the vinyl chloride resin composition of the present invention is not particularly limited as long as its melting point is higher than that of the vinyl chloride resin composition, and includes inorganic stabilizers that can be blended into the vinyl chloride resin composition, such as zeolite and hydrotalcite, as well as silicon dioxide (silica), titanium dioxide, aluminum oxide, zirconium oxide, zinc oxide, tin oxide, calcium carbonate, barium sulfate, talc, kaolin, barium titanate, aluminum nitride, silicon nitride, boron nitride, silicon carbide, and inorganic pigments. These may be used individually or in combination of two or more in any ratio. In particular, the (c) inorganic substance preferably includes at least one selected from the group consisting of zeolite, hydrotalcite, and inorganic pigments, and more preferably zeolite and / or hydrotalcite. Furthermore, if the vinyl chloride resin composition of the present invention contains other components described later, (c) the inorganic substance is preferably a substance different from these other components.
[0048] Here, zeolite is given by the general formula: M x / n ·[(AlO2) x (SiO2) y This is a compound represented by the general formula ]·zH2O (wherein M is a metal ion with valence n, x+y is the number of tetrahedra per monon lattice, and z is the number of moles of water). Examples of M in this general formula include monovalent or divalent metals such as Na, Li, Ca, Mg, and Zn, as well as mixtures thereof.
[0049] Furthermore, hydrotalcite is not particularly limited and includes carbonate-type hydrotalcite, nitrate-type hydrotalcite, sulfate-type hydrotalcite, chloride-type hydrotalcite, fluoride-type hydrotalcite, and perchlorate-substituted hydrotalcite. Among these, perchlorate-substituted hydrotalcite is preferred.
[0050] [Melting point] (c) The melting point of the inorganic substance must be higher than (a) the melting point of the vinyl chloride resin composition. (c) The melting point of the inorganic substance is not particularly limited, but may be 300°C or higher.
[0051] [Content percentage] (c) The inorganic content is preferably 3 parts by mass or more, more preferably 5 parts by mass or more, preferably 35 parts by mass or less, and more preferably 30 parts by mass or less, per 100 parts by mass of matrix vinyl chloride resin. (c) If the inorganic content is above the lower limit, the tensile elongation of the vinyl chloride resin molded article formed using the vinyl chloride resin composition at high temperatures can be well suppressed. Also, (c) if the inorganic content is below the upper limit, the tensile elongation of the vinyl chloride resin molded article formed using the vinyl chloride resin composition at low temperatures can be well maintained.
[0052] Furthermore, the total content of zeolite and hydrotalcite is preferably (a) 3 parts by mass or more, more preferably 5 parts by mass or more, preferably 35 parts by mass or less, and more preferably 30 parts by mass or less per 100 parts by mass of matrix vinyl chloride resin. (c) If the content of inorganic substances is above the lower limit, the tensile elongation of the vinyl chloride resin molded article formed using the vinyl chloride resin composition at high temperatures can be well suppressed. Furthermore, (c) if the content of inorganic substances is below the upper limit, the tensile elongation of the vinyl chloride resin molded article formed using the vinyl chloride resin composition at low temperatures can be well maintained.
[0053] <Other ingredients> Other components that the vinyl chloride resin composition of the present invention may optionally contain are, without particular limitation, those other than (a) matrix vinyl chloride resin, (b) plasticizer, and (c) inorganic substances, and include vinyl chloride resin fine particles and various additives. Additives are not particularly limited and include lubricants; stabilizers such as β-diketones and fatty acid metal salts; release agents; other dusting agents other than the vinyl chloride resin fine particles mentioned above; impact resistance improvers; antioxidants; antifungal agents; flame retardants; antistatic agents; fillers; light stabilizers; foaming agents; organic pigments; and the like. As for the additives that the vinyl chloride resin composition of the present invention may contain, for example, those described in International Publication No. 2016 / 098344 can be used, and the preferred content ratio can be the same as that described in International Publication No. 2016 / 098344.
[0054] [Vinyl chloride resin microparticles] In a vinyl chloride resin composition, vinyl chloride resin fine particles typically function as a dusting agent (powder flow improver). It is preferable that the vinyl chloride resin fine particles are manufactured by emulsion polymerization. Furthermore, in this invention, "resin fine particles" refers to particles with a particle diameter of less than 30 μm. Here, the vinyl chloride resin constituting the vinyl chloride resin fine particles can be the same as the vinyl chloride resin constituting the matrix vinyl chloride resin described above (a). Furthermore, the vinyl chloride resin constituting the vinyl chloride resin fine particles may be a cross-linked vinyl chloride resin. The method of cross-linking the vinyl chloride resin is not particularly limited; for example, it may be a chemical cross-linking method using a known cross-linking agent, or it may be a cross-linking method using radiation such as an electron beam.
[0055] [Average degree of polymerization] The average degree of polymerization of the vinyl chloride resin constituting the vinyl chloride resin fine particles is preferably 500 or higher, more preferably 700 or higher, preferably 2600 or lower, and more preferably 2400 or lower. If the average degree of polymerization of the vinyl chloride resin constituting the vinyl chloride resin fine particles used as a dusting agent is above the lower limit, the powder fluidity of the vinyl chloride resin composition will be improved, and the tensile elongation of the molded article obtained using the composition will be improved. Furthermore, if the average degree of polymerization of the vinyl chloride resin constituting the vinyl chloride resin fine particles is below the upper limit, the meltability of the vinyl chloride resin composition will be improved, and the surface smoothness of the vinyl chloride resin molded article formed using the composition will be improved.
[0056] [Average particle size] The average particle size of the polyvinyl chloride resin fine particles is usually less than 30 μm, preferably 10 μm or less, more preferably 5 μm or less, preferably 0.1 μm or more, and more preferably 1 μm or more. If the average particle size of the polyvinyl chloride resin fine particles is above the lower limit, the powder flowability of the polyvinyl chloride resin composition can be further improved without excessively reducing the size of the particles used as a dusting agent, for example. Furthermore, if the average particle size of the polyvinyl chloride resin fine particles is below the upper limit, the mellowability of the polyvinyl chloride resin composition is increased, and the surface smoothness of the formed polyvinyl chloride resin molded article can be further improved. In this invention, the "average particle size of the polyvinyl chloride resin fine particles" can be measured as the volume-average particle size by laser diffraction in accordance with JIS Z8825.
[0057] [Content percentage] The preferred content of the vinyl chloride resin fine particles is preferably 5% by mass or more, preferably 35% by mass or less, more preferably 30% by mass or less, and even more preferably 25% by mass or less, relative to the total of the matrix vinyl chloride resin and the vinyl chloride resin fine particles. If the content of vinyl chloride resin fine particles is above the lower limit, the powder flowability of the vinyl chloride resin composition can be further improved. Also, if the content of vinyl chloride resin fine particles is below the upper limit, the physical strength of the vinyl chloride resin molded article formed using the vinyl chloride resin composition can be further increased.
[0058] (Method for producing vinyl chloride resin composition) The vinyl chloride resin composition of the present invention can be produced by mixing the above components. That is, the method for producing the vinyl chloride resin composition of the present invention includes mixing at least (a) matrix vinyl chloride resin, (b) plasticizer, and (c) inorganic substance. In addition to the above components, the method for producing the vinyl chloride resin composition may optionally include the above other components. Here, the method of mixing the above (a) matrix vinyl chloride resin, the above (b) plasticizer, the above (c) inorganic substance, and other components added as needed is not limited. A preferred mixing method is to dry blend the components excluding the plasticizer and dusting agent (including vinyl chloride resin fine particles), and then sequentially mix in the plasticizer and dusting agent. The use of a Henschel mixer is preferred for dry blending. The temperature during dry blending is not particularly limited, but is preferably 50°C or higher, more preferably 70°C or higher, and preferably 200°C or lower.
[0059] (Vinyl chloride resin molded product) The vinyl chloride resin molded article of the present invention is obtained by molding the vinyl chloride resin composition of the present invention described above by any method. Since the vinyl chloride resin molded article of the present invention is formed using the vinyl chloride resin composition of the present invention described above, it exhibits excellent airbag deployment performance in high-temperature and low-temperature environments without the need for tear lines. Therefore, the vinyl chloride resin molded article of the present invention can be suitably used as an automotive interior material, such as the surface of an automotive instrument panel, where excellent light resistance is required.
[0060] <Method for forming a polyvinyl chloride resin molded product> Here, when forming a polyvinyl chloride resin molded body by powder slush molding, the mold temperature during powder slush molding is not particularly limited, but is preferably 200°C or higher, more preferably 220°C or higher, preferably 300°C or lower, and more preferably 280°C or lower.
[0061] Furthermore, when manufacturing a vinyl chloride resin molded article, the following method can be used without particular limitation. That is, the vinyl chloride resin composition of the present invention is sprinkled onto a mold at the above temperature range, left for 5 seconds to 30 seconds, the excess vinyl chloride resin composition is shaken off, and then left for 30 seconds to 3 minutes at any temperature. After that, the mold is cooled to 10°C to 60°C, and the obtained vinyl chloride resin molded article of the present invention is demolded from the mold. A sheet-like molded article that conforms to the shape of the mold is then obtained.
[0062] (Laminated structure) The laminate of the present invention comprises a foamed polyurethane molded body and the vinyl chloride resin molded body described above. The vinyl chloride resin molded body typically constitutes one of the surfaces of the laminate. Furthermore, since the laminate of the present invention has a vinyl chloride resin molded article formed using the vinyl chloride resin composition of the present invention described above, which exhibits excellent airbag deployment performance in high-temperature and low-temperature environments, it is suitably used as an automotive interior part, particularly as an automotive interior material for forming an automotive instrument panel.
[0063] Here, the method for laminating the foamed polyurethane molded body and the polyvinyl chloride resin molded body is not particularly limited, and for example, the following methods can be used. Specifically, (1) a method of preparing the foamed polyurethane molded body and the polyvinyl chloride resin molded body separately and then bonding them together by heat fusion, heat bonding, or using known adhesives; (2) a method of directly forming a foamed polyurethane molded body on the polyvinyl chloride resin molded body by reacting isocyanates and polyols, which are raw materials for the foamed polyurethane molded body, on the polyvinyl chloride resin molded body to carry out polymerization, and by foaming the polyurethane using a known method. Among these, the latter method (2) is preferred because the process is simple and it is easy to firmly bond the polyvinyl chloride resin molded body and the foamed polyurethane molded body even when obtaining laminates of various shapes. [Examples]
[0064] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples. In the following description, "%" and "parts" representing quantities refer to mass unless otherwise specified. Various measurements and evaluations in the examples and comparative examples were performed by the following methods.
[0065] <Low temperature flexibility> The polyvinyl chloride resin molded sheets (dimensions: 200 mm × 152 mm × 1 mm) obtained in the examples and comparative examples were punched out to a size of 10 mm × 40 mm, and the peak top temperature of the loss modulus was measured in accordance with JIS K7244-4, at a frequency of 1 Hz, a measurement temperature range of -90 °C to +100 °C, and a heating rate of 2 °C / min. The lower the peak top temperature of the polyvinyl chloride resin molded sheet, the better the low-temperature flexibility before heating (initial stage). <Tensile stretch> The tensile elongation [%] of the obtained polyvinyl chloride resin molded sheets at -35°C and 85°C was measured in accordance with ISO 527-1,2, by punching them out with a 5A dumbbell as described in ISO 527-2, and at a tensile speed of 100 mm / min. Then, the ratio of the tensile elongation [ε1] measured at 85°C to the tensile elongation [ε2] measured at -35°C ([ε1] / "ε2") was calculated. <Airbag deployment capability> [Airbag deployment test in a high-temperature (85°C) environment] The airbag deployment test under high temperature (85°C) conditions was conducted as follows. The instrument panel used for the airbag deployment test consisted of three layers: a surface layer, a foam layer, and a base layer. The surface layer was a molded sheet made of a polyvinyl chloride resin composition, the foam layer was polyurethane, and the base layer was polypropylene. In the airbag deployment test, the airbag body was inflated from the base layer side of the instrument panel, and the quality of airbag deployment was determined from the pattern of rupture of the molded sheet made of the polyvinyl chloride resin composition. At this time, the instrument panel was placed in a constant temperature bath set to a temperature higher than 85°C, and the airbag deployment test was performed when the surface material temperature reached 85°C. Specifically, the airbag deployment performance was evaluated based on the following criteria. Good: The airbags deployed without any problems. Defect: The polyvinyl chloride resin molded part stretches, preventing the airbag from deploying. [Airbag deployment test in a low-temperature (-35°C) environment] The airbag deployment test in a low-temperature (-35°C) environment was conducted as described above, except that the surface material temperature was set to -35°C. The airbag deployment performance was then evaluated based on the following criteria. Good: The airbags deployed without any problems. Defect: When the airbag deployed, the polyvinyl chloride resin molded material scattered.
[0066] (Example 1) <Preparation of vinyl chloride resin composition> Of the components shown in Table 1, all components except the plasticizers (trimellitic acid ester, sebacitic acid derivative, and epoxidized soybean oil) and polyvinyl chloride resin fine particles used as a dusting agent were mixed in a Henschel mixer. When the temperature of the mixture was 80°C or higher, the plasticizers were added and the mixture was dried up (this refers to the state in which the plasticizers are absorbed by the matrix polyvinyl chloride resin, which is the polyvinyl chloride resin, and the mixture becomes free-flowing). Subsequently, when the dried mixture cooled to a temperature of 70°C or lower, the polyvinyl chloride resin fine particles used as a dusting agent were added to prepare the polyvinyl chloride resin composition.
[0067] <Manufacturing of polyvinyl chloride resin molded products (sheets)> The obtained polyvinyl chloride resin composition was sprinkled onto a textured mold heated to 250°C, left to melt for a specified time, and then the excess polyvinyl chloride resin composition was shaken off. The textured mold containing the polyvinyl chloride resin composition was then placed in an oven set to 200°C, and after 60 seconds, the textured mold was cooled with cooling water. When the mold temperature had cooled to 40°C, a 200mm x 152mm x 1mm polyvinyl chloride resin molded sheet was demolded from the mold as a polyvinyl chloride resin molded product. The resulting polyvinyl chloride resin molded sheets were then measured or evaluated for tensile elongation and airbag deployment properties according to the method described above. The results are shown in Table 2.
[0068] (Examples 2-12, Comparative Examples 1-3) In the preparation of the vinyl chloride resin composition, the vinyl chloride resin composition and vinyl chloride resin molded articles were manufactured in the same manner as in Example 1, except that the compounding components were changed as shown in Table 1. Measurement and evaluation were then performed in the same manner as in Example 1. The results are shown in Table 2. [Table 1] [Table 2]
[0069] 1) Manufactured by Ningbo Taisho Co., Ltd., product name "S-70" (vinyl chloride resin, average particle size: 120μm, average degree of polymerization: 1300) 2) Manufactured by Tosoh Corporation, product name "Ryuron Paste (registered trademark) AD50" (cross-linked polyvinyl chloride resin, average particle size: 2.1 μm) 3) ZEST PQLTX (vinyl chloride resin fine particles, average degree of polymerization 800, average particle size 1.7 μm), manufactured by Shin-Daiichi Vinyl Chloride Co., Ltd. 4) Manufactured by Tosoh Corporation, product name "Ryuron Paste (registered trademark) 860" (vinyl chloride resin fine particles, average degree of polymerization 1600, average particle size 2.4 μm) 5) Manufactured by Kunshan ▲Wei▼Feng Chemical Co., Ltd., product name: “TOTM” 6) Manufactured by Kunshan ▲Wei▼Feng Chemical Co., Ltd., product name: ``DIDS'' 7) ADKEA Co., Ltd., product name "ADKEA Sizer O-130S" 8) Perchlorate-substituted hydrotalcite (manufactured by Kyowa Chemical Industry Co., Ltd., product name "Alkamizer (registered trademark) 5") 9) Na zeolite (manufactured by Mizusawa Chemical Industries, Ltd., product name "MIZUKALIZER DS") 10) Manufactured by Showa Denko Corporation, product name "Kalens DK-1" 11) Zinc stearate (Sakai Chemical Industry Co., Ltd., product name "SAKAI SZ2000") 12) Manufactured by ADEKA Corporation, product name "ADEKA Stub LA-63P" 13) Manufactured by ADEKA Corporation, product name "ADEKA Stub SC-131" 14) Manufactured by Shandong Xinhua Pharmaceutical Co., Ltd., product name: “Shandong Xinhua Aminodimethyluracil” 15) Manufactured by Hubei Chushengwei Chemical Co., Ltd., product name "ETHYLENEBISOLEAMIDE" 16) Manufactured by Dainichi Seika Co., Ltd., product name "DA PX 1720(A) Black" 17) Manufactured by Dainichi Seika Co., Ltd., product name "DA PX 1496 Yellow" 18) Manufactured by Dainichi Seika Co., Ltd., product name "PX-1050 White"
[0070] As shown in Table 2, in Examples 1 to 12, which used a vinyl chloride resin composition comprising (a) a matrix vinyl chloride resin, (b) a plasticizer, and (c) an inorganic substance, wherein (c) the inorganic substance has a higher melting point than the vinyl chloride resin composition, and when molded into a sheet, the ratio of the tensile elongation [ε1] measured at 85°C to the tensile elongation [ε2] measured at -35°C ([ε1] / "ε2") is 15 or less, it can be seen that a vinyl chloride resin molded article can be obtained in which the airbag can be properly deployed even in high-temperature environments (85°C) and low-temperature environments (-35°C) without the provision of a tear line. [Industrial applicability]
[0071] According to the present invention, it is possible to provide a vinyl chloride resin composition that can form a vinyl chloride resin molded article that can properly deploy an airbag even in high-temperature and low-temperature environments without providing a tear line. Furthermore, according to the present invention, it is possible to provide a vinyl chloride resin molded article formed from the above-mentioned vinyl chloride resin composition, and a laminate having the vinyl chloride resin molded article.
Claims
1. A vinyl chloride resin composition comprising (a) a matrix vinyl chloride resin, (b) a plasticizer, and (c) an inorganic substance, When formed into a sheet, the ratio of the tensile elongation [ε1] measured at 85°C to the tensile elongation [ε2] measured at -35°C ([ε1] / "ε2") is 15 or less. The inorganic substance (c) is a vinyl chloride resin composition having a higher melting point than the vinyl chloride resin composition.
2. The vinyl chloride resin composition according to claim 1, wherein the content ratio of the plasticizer (b) is 90 parts by mass or more per 100 parts by mass of the matrix vinyl chloride resin (a).
3. The vinyl chloride resin composition according to claim 1, wherein the content of the inorganic substance (c) is 35 parts by mass or less per 100 parts by mass of the matrix vinyl chloride resin (a).
4. The vinyl chloride resin composition according to claim 1, further comprising vinyl chloride resin fine particles.
5. The vinyl chloride resin composition according to claim 1, wherein the plasticizer (b) comprises at least one of trimellitic acid ester and sebaciate ester.
6. A vinyl chloride resin composition according to claim 1, used for powder molding.
7. A vinyl chloride resin composition according to claim 1, used in powder slush molding.
8. A vinyl chloride resin molded article obtained by molding a vinyl chloride resin composition according to any one of claims 1 to 7.
9. A polyvinyl chloride resin molded article according to claim 8, for use as the surface material of an automotive instrument panel.
10. A laminate comprising a foamed polyurethane molded body and a vinyl chloride resin molded body according to claim 8.
11. The laminate according to claim 10, for use in an automotive instrument panel.
Citation Information
Patent Citations
Automobile airbag door and process for producing the same
WO2009141863A1